MENINGKATKAN HASIL BELAJAR KEWIRAUSAHAAN MELALUI PENDEKATAN KONSTRUKTIVISME - Roskina, Roskina (Indonesian Journal of Educational Studies, 2018)
This research is a Classroom Action Research which aims to improve students' entrepreneurial learning outcomes through the Constructivism Approach. The results of the analysis show that what is obtained from quantitative descriptive analysis are as follows: (1) There is an increase in student learning outcomes with the increasing number of students in the high category, namely in Cycle I 10 students (30%) and Cycle II 20 students or 70%. The average score of mastery of material has increased by 10.04 (10.04%). (2) Students' completeness of learning increases after being given learning by using the constructivism approach at each meeting in Cycle II. From the results of the above analysis it can be concluded that the constructivism approach can improve students' entrepreneurial learning outcomes.